Gibberellin biosynthesis and signalling in Arabidopsis root growth - Barker, Richard (2011)
Using targeted expression of a constitutively active repressor of GA signalling Susana Ubeda-Tomas et al., (2007) demonstrated that GA action in endodermal cells is necessary for correct root growth. However, GUS studies have shown the final and penultimate GA-biosynthetic genes are not expressed in the endodermis, indicating movement of GAs may be required. This study used the targeted mis-expression of GA degrading enzymes in Col-0 and the attempted targeted rescue of GA biosynthetic and signalling mutants, using the corresponding GA metabolic or signalling component, to gain an insight into the localisation of important GA biosynthesis and signalling sites.